The lineages of play. (29th November 2016) - Bateman, Chris
Abstract : Does each generation invent its own ways of playing, or is there an historical connectivity behind play that can be traced backwards through time? Building on aesthetics of play on the one hand, and genealogical lineages of player practices on the other, this article sketches an argument for the continuity of play, and the connectivity between art, toys and games, as well as between human and animal play. The article is structured both by the aesthetic motives for play (a tentative inventory of motivations for pursuing play of any kind) and by a novel concept of logarithmic time. This method of discussing the past simplifies historical references into arbitrary but carefully structured intervals in order to describe the transitions and developments (whether putative or archaeological) in the player practices that constitute play. The result is a whistle-stop journey 'through time' in order to examine the lineages of play.